Os movimentos sociais na crise financeira global: questões e polêmicas - Leonardo de Araújo e Mota (Ciências Sociais Unisinos)
In the 1990s, anti-globalization movements began contesting the effects of neoliberal policies and their social consequences, organizing several protests in Seattle (1999), Genoa (2001), New York (2002), targeting institutions such as the G-8 group or the World Trade Organization (WTO). After the financial crisis of 2008 in the United States, other social movements of resistance to capitalism began to protest in the streets of the U.S. and Europe, among which are the Indignados (Spain), Occupy Wall Street (USA) and Geração à Rasca (Portugal). The purpose of this article is to perform a theoretical analysis, based on contemporary social science authors, of the social movements that emerged after the financial crisis of 2008, placing them in the context of contemporary capitalism. It concludes that, despite the increased incidence of such social movements worldwide, the present context of economic recession still causes high unemployment rates in the countries most affected by the crisis, the environment remains threatened and most political parties suffer a big crisis of representation within civil society.